PECULIUM PROCESS IN RECEIVABLES RIGHTS - Nezir, Funda (International Scientific Journal Vision, 2024)
Peculium process is one of the most common types of legal transactions in daily life because it affects a right in the property. It is a legal transaction that directly affects a right in the assets of the person making the disposition, transferring, restricting, changing or terminating that right to another person. For this reason, it is important to evaluate the change made by the peculium process in the field of movable and immovable rights and relative rights. In this direction, the discussion of the intangibility of the receivables in the transfer of the receivable and the transfer of the receivables in the field of relative rights and the discussion of intangibility of the release and the intangibility of the reason in the release, which is a peculium process, were discussed and the results of the transaction were evaluated